The Importance of Strategic Planning, Employee Performance, and Supplier Relationship Management in F&B Business - Mulia Khoerul Hakim; Agus Prayitno (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
This study presents a literature review that investigates the role of strategic planning in enhancing employee performance and strengthening supplier relationship management within the food and beverage (F&B) business sector in Semarang City. Strategic planning, as the independent variable, is critical in defining the company’s vision, mission, objectives, and policies, which directly influence the productivity, effectiveness, and engagement of employees, the dependent variable. By systematically analyzing a wide range of literature sources, including peer-reviewed journals, articles, and other reputable publications, this study highlights the multifaceted benefits of effective strategic planning. The analysis reveals that organizations that implement clear and well-structured strategic plans are more likely to experience improved employee motivation, higher performance levels, greater job satisfaction, and increased employee loyalty. Additionally, the study emphasizes the importance of establishing and maintaining strong, strategic relationships with suppliers, which contribute to operational stability, efficient supply chain management, and enhanced competitiveness in the F&B industry. The findings suggest that strategic planning and supplier relationship management are interrelated and mutually reinforcing processes that help businesses anticipate market demands, optimize resource allocation, and respond effectively to operational challenges. Ultimately, the integration of these two factors provides a sustainable competitive advantage, enabling F&B businesses in Semarang to improve internal performance while simultaneously strengthening external partnerships. This study underscores the necessity for managers and business owners to prioritize strategic planning and supplier relationship management as essential components of long-term business success in a highly dynamic and competitive market environment.